Metal complex-assisted activation of small molecules. from NO to superoxide and peroxides - Ivanovic-Burmazovic, Ivana; van Eldik, Rudi (Dalton Transactions, 2008)
Transition metal centres are one of the primary targets for nitric oxide (NO), superoxide (Ȯ) and hydrogen peroxide (H O), which are small molecules present in a biological milieu, and of industrial and environmental interest. Coordination to a metal centre modulates their redox behaviour in such a way that they become activated for an inner-sphere oxidation or reduction, depending on the electronic and redox properties of a particular transition metal ion. Since the related redox reactions play multiple roles in physiological and pathophysiological processes, as well as in chemical catalysis in terms of synthetic applications and exhaust gas purification, the elucidation of the mechanisms of the elementary reaction steps behind these complex processes is of fundamental importance. This review concentrates on our work in this area, where by applying low temperature and high pressure kinetic and thermodynamic techniques we shed more light on the mechanisms of the particular reaction steps involved in the activation of NO, Ȯ and various peroxides. The studies include work on solvent exchange reactions that control the binding of small molecules to the metal centre and subsequent electron-transfer processes. We paid special attention to different iron and manganese complexes with heme and non-heme ligand systems. © The Royal Society of Chemistry.